Human immunodeficiency virus and other blood-borne viral pathogens in the athletic setting (Pediatrics, 1999)
Because athletes and the staff of athletic programs can be exposed to blood during athletic activity, they have a very small risk of becoming infected with human immunodeficiency virus, hepatitis B virus, or hepatitis C virus. This statement, which updates a previous position statement of the American Academy of Pediatrics,1 discusses sports participation for athletes infected with these pathogens and the precautions needed to reduce the risk of infection to others in the athletic setting. Each of the recommendations in this statement is dependent upon and intended to be considered with reference to the other recommendations in this statement and not in isolation.